Второй этап переводоведческого анализа: выбор соответствий оценочной лексики в языке и культуре перевода (На материале оценочной лексики исторического романа) - Островский, Д.О. (Культура народов Причерноморья, 2004)
The article handles the second stage of source language texts translation process, namely finding the appropriate equivalents in the foreign language culture. The object of the analyses under consideration is appraisal lexicon. The subject of the analyses are historical relies and historical symbols.